MOTIVASI ORANG TUA DALAM PENDIDIKAN AKHLAK (STUDI KASUS WALI SANTRI DI PONDOK PESANTREN HIDAYATUL MUBTADI’IN TASIKMADU MALANG) - Roudlatul Fitriyah; Abdul Jalil; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Parental motivation is one of the alternative methods used to arouse children's enthusiasm or intention to study at the Hidayatul Mubtadi'in Islamic Boarding School in Tasikmadu Malang. This study focuses on the motivation of parents, ways of educating morals as well as inhibiting and supporting factors in the process of moral education at the Hidayatul Mubtadi'in Islamic Boarding School. To achieve this goal, the researcher uses a phenomenological-based qualitative approach using a case study approach. Researchers found the results of this study include the motivation of parents in moral education at the Hidayatul Mubtadi'in Islamic Boarding School. the implementation of the research includes activities in Islamic boarding schools, providing motivation, encouragement and intention to children to continue learning Islamic religious knowledge and moral education in Islamic boarding schools, because studying Islamic religion is very important and good moral education is only in Islamic boarding schools because in formal schools , children can only study general education.